The Application of The Condition Construction Development Simulation Reflection (CCDSR) Learning Model Assisted by A Combination of Real-Virtual Experiments on Students' Science Process Skills on Static Fluid Material - Aas Aisyah; Duden Saepuzaman; Saeful Karim (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
The science process skills possessed by students are still in the low category. This is caused by a lack of learning activities that facilitate students to train and develop their existing science process skills in learning. This research aims to determine the improvement of science process skills through the application of the CCDSR learning model to static fluid material. The method used in this research is a quantitative method with a one group pretest posttest research design involving class XI MIPA students with a total of 31 participants. Data collection was carried out using scientific process skills test instruments and then analyzed using normality tests, homogeneity tests, hypothesis tests and N-Gain tests assisted by IBM SPSS version 29 software. Based on the results of data processing, the significance value of the normality test for the pretest was obtained at 0, 10 < 0.05, while for the posttest it was 0.086 > 0.05. Then, the homogeneity test has a significance value of 0.555 > 0.05, and the t test is <0.001. Meanwhile, the average increase in science process skills obtained from the N-Gain test was 0.62 in the medium category. Based on the results of the analysis, it can be concluded that applying the CCDSR learning model in learning can improve students' science process skills in static fluid material.